2006
DOI: 10.1152/ajplung.00269.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 induces Nox4 NAD(P)H oxidase and reactive oxygen species-dependent proliferation in human pulmonary artery smooth muscle cells

Abstract: Transforming growth factor-beta1 (TGF-beta1) is abundantly expressed in pulmonary hypertension, but its effect on the pulmonary circulation remains unsettled. We studied the consequences of TGF-beta1 stimulation on freshly isolated human pulmonary artery smooth muscle cells (HPASMC). TGF-beta1 initially promoted differentiation, with upregulated expression of smooth muscle contractile proteins. TGF-beta1 also induced expression of Nox4, the only NAD(P)H oxidase membrane homolog found in HPASMC, through a signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
321
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 363 publications
(348 citation statements)
references
References 38 publications
25
321
1
1
Order By: Relevance
“…Pulmonary smooth muscle cells and fibroblasts: NOX4-Studies in pulmonary fibroblasts and smooth muscle cells revealed the expression of p47phox, p67phox, p22phox and NOX4, and demonstrated increased production of ROS in response to inflammatory mediators, such as tumor necrosis factor β (TNF-β) or transforming growth factor β (TGF-β), which is primary associated with selective upregulation of NOX4 (185)(186)(187)(188). In addition, NOX4 expression is also induced by other stimuli, including hypoxia/ischemia, shear stress, and ER stress, but to date no information appears to be available regarding the NOX4 promoter or its transcriptional regulators (6,16,81).…”
Section: Functional Aspects Of Nox In Other Lung Cell Typesmentioning
confidence: 99%
See 3 more Smart Citations
“…Pulmonary smooth muscle cells and fibroblasts: NOX4-Studies in pulmonary fibroblasts and smooth muscle cells revealed the expression of p47phox, p67phox, p22phox and NOX4, and demonstrated increased production of ROS in response to inflammatory mediators, such as tumor necrosis factor β (TNF-β) or transforming growth factor β (TGF-β), which is primary associated with selective upregulation of NOX4 (185)(186)(187)(188). In addition, NOX4 expression is also induced by other stimuli, including hypoxia/ischemia, shear stress, and ER stress, but to date no information appears to be available regarding the NOX4 promoter or its transcriptional regulators (6,16,81).…”
Section: Functional Aspects Of Nox In Other Lung Cell Typesmentioning
confidence: 99%
“…Studies in isolated smooth muscle cells indicated that NOX4 expression in freshly isolated cells rapidly declines with multiple passages, in close association with loss of smooth muscle differentiation markers such as smooth muscle α-actin (SMA), myosin heavy chain (186,190). Subsequent studies with NOX4-targeted siRNA demonstrated that NOX4 is required for the expression of smooth muscle differentiation markers, and maintenance of SMA-based stress fibers (190).…”
Section: Functional Aspects Of Nox In Other Lung Cell Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…The Nox4 isoform has been generally considered to be constitutively active. It was recently found that the insulin receptor [156], toll-like receptor 4 [125], transforming growth factor β1 [145,146], and possibly interleukin 1β [39,57,59] all required Nox4 activity. In adipocytes, overexpression of Nox4 was not sufficient to increase basal levels of ROS but required insulin stimulation, arguing for a regulated Nox4 activity.…”
Section: Nadph Oxidase Expression and Function In Vascular Injurymentioning
confidence: 99%